Effects of climate change on migration in Latin America and Caribbean: a scoping review - Cabieses, Báltica; Huerta, Catalina (Frontiers in Climate, 2024)
Climate change-induced natural disasters such as hurricanes, landslides, forest fires, and changes in precipitation directly affect rural sectors that depend on field production and other dimensions of everyday life. This generates the mobilization of people from their homes to safer places within the same country or across borders. There is a lack of information on the impacts of climate change on environmental migrants in Latin America and the Caribbean (LAC). This scoping review aims to describe the scientific evidence of the health effects of climate change on migrant in LAC. The review was conducted using databases from PubMed, Web of Science (WoS), and Google Scholar in English, Spanish and Portuguese. After screening the title, abstract, and full text of identified hits (n = 726), 31 records were finally included. Evidence indicates that climate change relates to health and healthcare, psychosocial and infrastructure dimensions among migrants in LAC. Health effects refer to limited access to healthcare, underdiagnosis, increased susceptibility to diseases and mental health conditions like stress and anxiety. Psychosocial dimensions refer to a heightened risk of sexual and gender-based violence, social marginalization, family separation, and loss of identity and culture. Infrastructure refers to environmental degradation and agricultural and urban infrastructure destruction. Multiple adaptations to these conditions are described among migrant populations in the region. Recommendations for improvements are presented. This scoping review suggests climate change’s significant health, psychosocial, and infrastructural associations with migrants in Latin America.